Studi Komparatif Tentang Sistem Pemilihan Presiden di Indonesia Dalam Undang-Undang dan Fiqh Siyasah - Takdir, Takdir; Syahruni, Devi Shinta (Datuk Sulaiman Law Review (DaLRev), 2022)
This thesis discusses a comparative study of the presidential election system in Indonesia in Islamic law and law.This study aims: to find out the provisions of the presidential election in Islamic law, tofind out the provisions of the presidential election in Islamic law, to find out the provisions of the presidential election in Islamic law, to find ou the mechanism of the presidential election in Indonesia in Fiqh Siyasah. The type of research used is library research using a normative juridical approach. Data collection techniques in this study are data collection by means of searching, reading and recording activities from written works in the form of books or sources related to the discussion. The results of the research from this thesis that the presidential election system in Indonesia in the laws and Islamic law contained in Law No. 7 of 2017 explained that the presidential and vice presidential election system is a series with the general election of members of the people’s representative council which is held once every five years, the presidential andvice presidential election system is conducted in a direct, public, free, secret, honest and fair manner The election of the president obtains strong support from the people so that they are able to carry out the functions of state government power in the context of achieving national goals. It is also explained that general elections in Islam are contained in Q.S An-Nisa Verse 59, it is explained that Allah obliges Muslims to obey ulil amri from among them. Ulim amri is a leader and commands to obey a leader. So, this shows that the obligation to appoint a leader for Muslims is obligatory, even the basic principles used in general elections already exist and are recognized by Islam. In the rules of Islamic law, the election of a fair leader is the goal, while the general election of a fair leader is the goal, while the general election is wasilah. As for the mechanism of the presidential election system in Indonesia and Islamic law, boh use deliberation as a method to elect a president. If in Islam deliberation to elect a president. If in Islam deliberation to elect the President, in Indonesia the model of Presidential election by the DPR is replaced by direct election by the people. In Islam also when a. When the president is elected, all the people must make a promise.